TRANSAKSI JUAL BELI ONLINE DAN MANAJEMEN RESIKO PERSPEKTIF EKONOMI SYARIAH DI KOLAKA JUAL BELI (KJB) - Engseng Engseng; Akmir Akmir (Jurnal Syariah Hukum Islam, 2019)
Kolaka Jual Beli (KJB) is an online transaction group using the Facebook application that is carried out by the community, especially in Kolaka Regency with the Pre-order system or the Salam contract. This group aims to facilitate entrepreneurs in selling goods or services and make it easier for consumers to find the goods or services needed. The formulation of the problem in this study is how to buy and sell transactions online according to the perspective of the Islamic economy in Kolaka Sale and Purchase (KJB) and how to manage the risk of buying and selling online transactions according to the Islamic economic perspective in Kolaka Jual Beli (KJB). The purpose of this study is to determine the online buying and selling transactions according to the Islamic economic perspective in the buying and selling kolaka and knowing the risk management of online buying and selling transactions according to the Islamic economic perspective in the buying and selling kolaka (KJB). The research method used is a descriptive type of research with a qualitative approach that is subjected to online buying and selling transactions and risk management in the Islamic economic perspective. Then the research procedure carried out includes intensive observation (observation, documentation, and interviews) about online buying and selling transactions and risk management from the perspective of the Islamic economy in Kolaka Sale and Purchase (KJB). The results of this study indicate that the application of buying and selling online with the salam contract carried out by group members is not in accordance with the proper harmony and terms of the salam contract due to a lack of understanding of the salam contract system. and the risk management used by producers and consumers is very good as a solution if a problem occurs. Based on existing practices, it can be concluded that the implementation of the salam contract is not in accordance with the principles of the Qur'an and Hadith or especially Islamic economics